1987
DOI: 10.1016/s0006-3495(87)83317-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and structural basis of resting and use-dependent block of sodium current defined using disopyramide analogues

Abstract: The effects of disopyramide (Norpace) and 14 closely related structural analogues on the Na current of voltage clamped squid axons were examined to determine which physico-chemical properties and which changes in the structure of the Norpace molecule can alter the nature of its sodium channel blocking actions. Conventional voltage clamp technique for internally perfused giant axons was used. Axons were exposed to 100 microM concentrations via the internal perfusion solution, and the actions of the 15 analogues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
0
15
1
Order By: Relevance
“…Recent results obtained in squid axons with QX-314 and QX-222 (Yeh & Tanguy, 1985) and with disopyramide and analogues (Yeh & Ten Eick, 1987) indicate a slowing of recovery as the membrane is hyperpolarized and give additional support for the activation gate trapping model. In cardiac muscle, disopyramide shows similar potential dependence of the time constant of recovery from use-dependent block, when the membrane potential is changed by using variable potassium concentrations in the perfusion solution (Gruber et al, 1986).…”
Section: Introductionmentioning
confidence: 73%
“…Recent results obtained in squid axons with QX-314 and QX-222 (Yeh & Tanguy, 1985) and with disopyramide and analogues (Yeh & Ten Eick, 1987) indicate a slowing of recovery as the membrane is hyperpolarized and give additional support for the activation gate trapping model. In cardiac muscle, disopyramide shows similar potential dependence of the time constant of recovery from use-dependent block, when the membrane potential is changed by using variable potassium concentrations in the perfusion solution (Gruber et al, 1986).…”
Section: Introductionmentioning
confidence: 73%
“…Precisely, sodium ions are suspected to influence the drug concentration in the receptor pool. As proposed by Cahalan and Aimers 18 and recently by Yeh and Ten Eick, 33 Na + could control drug access, that is, the larger the number of charges moving through the open channel, the smaller might become the likelihood that a blocking molecule reaches the receptor area, and vice versa. One reason for such an antagonism might be electrostatic repulsion for the case that cationic drug molecules are going to block the Na + channel.…”
Section: Properties Of Antiarrhythmic Drug Binding To Cardiac Namentioning
confidence: 99%
“…Similar slope factors have also been recently reported for block of sodium channels by lidocaine in cardiac myocytes 30 and for block of sodium channels in the squid giant axon by analogues of disopyramide. 44 These results indicate that the dependence of fast channel block on membrane voltage (Figure 2) may be due primarily to a voltage dependence of the availability of a highaffinity channel state, rather than a voltage dependence of the binding and/or unbinding rate constants (k t or /,).…”
Section: -35mentioning
confidence: 83%
“…Previous studies in nerve have shown that the presence of external sodium ions can markedly reduce the slope for voltage-dependent block for QX-314, 36 as well as some analogues of disopyramide. 44 However, additional studies are needed to confirm this for RAC109.…”
Section: -35mentioning
confidence: 98%